Synthesis and characterization of novel organometallic chromium hexacarbonyl derivatives via ligand (L) substitution, where L = tris (3-methylphenyl) arsine, tris (M-fluorophenyl) phosphine and tris [3, 5-Bis (trifluoromethyl) phenyl] phosphine - Muhammad Yazid, Mohamad Yunus (2012)
The aim of the research study is to substitute the carbonyl ligand on chromium complexes in order to result in novel organometallic monocrystal compounds for crystal structure elucidation followed by physical and chemical characterization. Derivatives of Chromium Carbonyl are prepared by reaction with a number of tertiary phosphines and arsenic ligands which have the potential to result in novel organometallic compounds. Three different ligands were used to produce novel organornetallic monocrystal compounds which are Tris(3-methylphenyl)Arsine, Tris(m-flurophenyl)Phosphine, and Tris[3 ,5-bis(trifluoromethyl)phenyl]Phosphine. Of these, the substitution reaction using Tris(m-fluorophenyl)Phosphine resulted in the formation of crystals with pale yellow colour. Monocrystal x-ray diffraction on a resulted in the novel crystal structure determined as trans-Tetracarbonylbis[tris(3fluorophenyl)phosphane]chromium(0) with molecular formula Cr(C 1 8H12F3P)2(CO)4. Infrared Spectroscopy (IR) and Nuclear Magnetic Resonance (NMR) further compliment the X-ray diffraction results. In this novel structure, the Cr atom is octahedrally coordinated by four carbonyl ligands and two tertiary phosphanes, which are located trans to each other with a fluorine atom in the meta-position on each phenyl ring. The compound crystalises in the monoclinic system with space group P2 1 /c and with an average Cr-P bond length of 2.3327 A and average Cr-CO bond length of 1.8869 A. This final year project meets international standards and led to an International Union of Crystallography (1UCr) journal publication, specifically in Acta Crystallographica Section E; (2011) with the title trans-Tetracarbonylbis [tris(3-fluorophenyl) phosphane]chromium(0).